Collective motion of self-propelled chemical garden tubes. Issue 23 (26th May 2022) - Kumar, Pawan; Wang, Qingpu; Horváth, Dezső; Tóth, Ágota; Steinbock, Oliver
Abstract : In H2 O2 solutions, manganese-containing chemical garden tubes can self-propel due to the catalytic production and ejection of oxygen bubbles. Abstract : In H2 O2 solutions, manganese-containing chemical garden tubes can self-propel due to the catalytic production and ejection of oxygen bubbles. Here, we investigate the collective behavior of these self-assembled precipitate tubes. In thin solution layers, the tubes show definite autonomous dynamics with only weak interactions that result from fluid motion around the moving units and directional changes during collisions. In thick solution layers with convex menisci forcing spatial confinement, the tubes undergo cycles of self-assembly and dispersion. This collective motion results from the rhythmic creation of a large master bubble around which the tubes align tangentially.